Low-Temperature Solution-Processed ZnSnO Ozone Gas Sensors Using UV-Assisted Thermal Annealing. Issue 11 (1st November 2022) - Lin, Yan-Fong; Jiang, You-Yi; Huang, Bo-Lin; Huang, Po-Yen; Hsueh, Wen-Jeng; Huang, Chun-Ying
Abstract : Ultraviolet-assisted thermal annealing (UVTA) has been widely used to fabricate solution-processed amorphous oxide semiconductor (AOS)-based transistors and photodetectors. However, this method has not been used for AOS-based gas sensors, even though AOS is a good gas sensing material. This study determines the effect of UVTA on the electrical properties of In-free amorphous ZnSnO (ZTO) thin films and their ozone (O3 ) gas sensing characteristics. UV light from a Mercury lamp has sufficient energy to decompose the organic- and hydrogen-based impurities completely, which promotes the formation of metal oxide networks, so the quality of ZTO films is greatly increased by increasing treatment time. A relatively high gas response of 1.42 with a fast response/recovery time (124/78 s) is achieved. This strategy allows the fabrication of ZTO gas sensors at low temperature (150 °C) and is applicable to flexible electronics.